2023
DOI: 10.1080/0886022x.2023.2185468
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal syndrome misdiagnosis may be reduced using inferior vena cava ultrasound to assess intravascular volume and guide management

Abstract: Hepatorenal syndrome (HRS) is a diagnosis of exclusion defined as acute kidney injury (AKI) with cirrhosis and ascites, with serum creatinine unresponsive to standardized volume administration and diuretic withdrawal. Persistent intravascular hypovolemia or hypervolemia may contribute to AKI and be revealed by inferior vena cava ultrasound (IVC US), which may guide additional volume management. Twenty hospitalized adult patients meeting HRS-AKI criteria had IVC US to assess intravascular volume after receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The data showed a great variability of IVCD and IVCCI in patients with an AKI that was suspected of being HRS; according to these data, the reclassification of the subjects in terms of depleted volume, expanded volume, and increased intraabdominal pressure requires a different approach. These results were confirmed by other studies which concluded that 40% of the patients were misdiagnosed as HRS-AKI and treated according to the measurements of IVCD and IVCCI that suggested hipo-or hypervolemia; their renal function was improved with supplementary hydration or an increase in diuretics [58].…”
Section: Imaging Studiessupporting
confidence: 82%
“…The data showed a great variability of IVCD and IVCCI in patients with an AKI that was suspected of being HRS; according to these data, the reclassification of the subjects in terms of depleted volume, expanded volume, and increased intraabdominal pressure requires a different approach. These results were confirmed by other studies which concluded that 40% of the patients were misdiagnosed as HRS-AKI and treated according to the measurements of IVCD and IVCCI that suggested hipo-or hypervolemia; their renal function was improved with supplementary hydration or an increase in diuretics [58].…”
Section: Imaging Studiessupporting
confidence: 82%
“…[46] A recent study on pulmonary artery catheterization in cirrhosis-AKI showed that 62% of patients diagnosed with HRS by clinical criteria have elevated pulmonary capillary wedged pressure and were counterintuitively started on diuretics. [47] Patients can be better assessed for volume resuscitation in AKI using IVC dynamics, [48] and incorporation of POCUS is recommended in an updated HRS-AKI management algorithm. [16] While our institutional protocol for the management of HRS-AKI entails treating these patients in the liver ICU, we recognize that many other institutions' HRS-AKI protocol entails treating them in step-down units on the medical ward while they are on terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of POCUS in classifying the type of AKI in cirrhosis is an important evolving domain in HRS-AKI management 46 . A recent study on pulmonary artery catheterization in cirrhosis-AKI showed that 62% of patients diagnosed with HRS by clinical criteria have elevated pulmonary capillary wedged pressure and were counterintuitively started on diuretics 47 . Patients can be better assessed for volume resuscitation in AKI using IVC dynamics, 48 and incorporation of POCUS is recommended in an updated HRS-AKI management algorithm 16 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 82 ] reported 64% of 53 patients initially presumed to have HRS-AKI had intravascular hypovolemia or hypervolemia, or intra-abdominal hypertension by IVC ultrasound assessment, and 35% improved AKI following IVC ultrasound-guided volume management, making the diagnosis of HRS-AKI unlikely. In our study of 20 patients presumed to have HRS-AKI, 75% had intravascular hypovolemia or hypervolemia by IVC ultrasound [ 83 ]. Forty percent improved AKI with additional IVC ultrasound-guided volume management and had been misdiagnosed as HRS-AKI.…”
Section: Clinical Utility Of Cardiac and Ivc Ultrasoundmentioning
confidence: 99%